A cleanser formulated with Tris (hydroxymethyl) aminomethane and l‐arginine significantly improves facial acne in male Thai subjects. (26th July 2019) - Kumtornrut, Chanat; Manabe, Siyarat Dilokphongyotin; Navapongsiri, Marut; Okutani, Yuri; Ikegaki, Shinichi; Tanaka, Noriyuki; Hashimoto, Hiroshi; Songsantiphap, Chankiat; Wantavornprasert, Kittipong; Khamthara, Jenvajee; Takagi, Yutaka; Asawanonda, Pravit
Abstract: Background: Acne is one of the most common skin problems among human populations. A facial cleanser formulated with alkyl ether carboxylate (AEC) and alkyl carboxylate (AC) can improve acne by cleansing sebum on facial skin but cannot effectively remove keratotic plugs in the skin pores. Recently, we confirmed that Tris (hydroxymethyl) aminomethane and L‐arginine (Tris/Arg) is able to reduce sebum levels, disrupt keratotic plugs in vitro and decrease pore size on facial skin. Objective: To compare the efficacy of the Tris/Arg‐formulated cleanser with the AEC/AC cleanser in Thai subjects with acne. Methods: We designed a randomized, double‐blind, controlled, parallel trial. Thirty‐four male Thai subjects with mild to moderate acne were assigned to one of two groups: one group used the Tris/Arg cleanser while the other used the AEC/AC‐based cleanser twice a day for 4 weeks. Results: After 4 weeks, significant decreases in noninflammatory acne were observed in both groups, yet significant decreases in inflammatory acne were only observed in the Tris/Arg cleanser group. The sebum level prior to and 30 minutes after facial washing showed no change in either group. The average pore size with keratotic plugs on the cheeks was significantly decreased in the Tris/Arg group. More than half of subjects in both groups observed acne improvement but more subjects in the Tris/Arg group noted pore size improvement. Conclusion: The Tris/Arg formulated cleanser has a high efficacy for significantly reducing both noninflammatory and inflammatory acne accompanied by decreases in pore size with keratotic plugs in male Thai subjects.